MAENGKET SEBAGAI SARANA PENDIDIKAN SENI MELALUI AKTIVITAS APRESIATIF DAN KREATIF - Pandaleke, Stefanny; Maragani, Meyltsan (GETER, 2019)
The efforts to develop student potential, preservation and development of art through appreciative and creative activities are important things to do. Maengket, as a traditional art in North Sulawesi has the potential as a means of art education through appreciative and creative activities. The discussion in this article is about how the process of art appreciation and creation in learning Maengket as a learning material for Cultural Arts, so that students gain an aesthetic experience. Appreciation activity begins with the introduction or description about Maengket. Then the second step is the analysis of the text from Maengket which includes music and dance movements. The next step is evaluation by giving a summary of the material and looking on the student responses to activities in the previous steps. Furthermore, the creation activities in Maengket learning stand on the concepts and ideas that have been obtained in previous appreciation activities. Each student is given the freedom to express every ideas and express it honestly and personally. Thus, Maengket learning as teaching material in Arts and Culture learning can be more optimized. Keywords: Art Education, Appreciation, Creation, Maengket